The Effect of Individual Religiosity on Visits to Religious Tourism - Ahmad Saefulloh; Miftakhul Khasanah (International Journal of Integrated Science and Technology, 2024)
This research aims to determine the influence of religiosity, the attractiveness of religious tourism and the quality of sharia tourism bureau services on tourists' decisions to visit the Gedhe Kauman Mosque, Yogyakarta. This research uses a quantitative type of research, using primary data. The sampling technique was purposive sampling with 200 respondents as the research sample. Data were analyzed using SmartPLS 3.0. The research results show that the religiosity variable does not have a significant effect on tourists' decisions to visit the Gedhe Kauman Mosque in Yogyakarta, while the variables of religious tourism attraction and the quality of sharia tourism bureau services have a positive and significant effect on tourists' decisions to visit the Gedhe Kauman Mosque in Yogyakarta.